Perlindungan Hukum bagi Konsumen atas Pencantuman Klausula Eksoner dalam Bisnis Pinjam-Meminjam Uang Berbasis Teknologi Informasi di Indonesia - Rahmawati, Intan Ayu Yulia; Yuliati, Yuliati; Santoso, Budi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
The purpose of this study is to analyze the legal basis for consumer protection and forms of consumer protection for the inclusion of exoneration clauses in financial technology peer to peer lending. This paper uses normative juridical methods for reviewing and analyzing the application of rules, regulations, and positive legal norms contained in the legislation. The analysis technique uses analytical prescriptive. The results of the study show that there are currently three regulations relating to consumer protection of Financial Technology Peer to Peer Lending in Indonesia, i.e. the Consumer Protection Act, Financial Services Authority Regulation Number 77/ POJK.01/2016 concerning Financial Technology Peer to Peer Lending, and the Law Number 11 of 2008 concerning Information and Electronic Transactions. The form of consumer protection for consumers over financial technology peer to peer lending with addition of clause exoneration is to impose sanctions on the organizer in the form of warning letters, fines, restrictions on business activities, and revocation of licenses granted by the Financial Services Authority. If through giving sanctions the consumer still feels disadvantaged, the consumer can resolve the problem through the District Court or outside the court by the Consumer Dispute Resolution Board.